Generational Diversity in the Workplace: A Systematic Review in the Hospitality Context - Malinvisa Sakdiyakorn (2019)
© 2017, © The Author(s) 2017. This article marks the first systematic review that focuses on generational diversity in the hospitality workplace in the period from 2000 to 2016. A comprehensive search was conducted in the five dominant databases, namely, Scopus, SAGE, Emeralds, Science Direct, and EBSCOhost’s Hospitality and Tourism Complete, resulting in 49 articles for systematic content analysis. This article maps out the existing landscape of generational studies within a hospitality context before providing five areas of recommendations for future studies to fully capture the intricacy of the generational phenomenon. This study serves as a funnel for academics and practitioners within the hospitality field as it gears their attention and research directions toward the crucial, yet underexamined, context of generational studies.